Formulasi Beton yang Mengalir Sendiri di Laboratorium Fakulas Teknik Universitas Batanghari - Suhendra Suhendra; Fadlan Fadlan (Jurnal Talenta Sipil, 2022)
The compaction of concrete is carried out with a vibrating device or using an awl.  One solution in facing problems in concrete compaction is to use the Self Compacting Concrete (SCC) method or also called self-flowing concrete.  This study aims to obtain a mixture formula / composition of laboratory-scale SCC-making materials that meet the SCC acceptance criteria. The mixing method is carried out by trial and error by referring to the values of Flowability, Workability, and Passing Ability. The planned SCC concrete quality is fc' 35 MPa. The added ingredients used are the superplasticizer Sika Viscoflow 3660 LR dose variations of 1.2%, 1.6% and doses of 2% against the weight of cement and powder. The results showed that the established composition was quite good and met the criteria for acceptance of SCC concrete.  The quality of the plan was achieved with the addition of 2% sika viscoflow to fc' 35 MPa.